Key Generator to Encryption Images Based on Chaotic Maps - Yousif, Ahmed; Kashmar, Ali H. (Iraqi Journal of Science, 2019)
It is known that images differ from texts in many aspects, such as high repetition and correlation, local structure, capacitance characteristics and frequency. As a result, traditional encryption methods can not be applied to images. In this paper we present a method for designing a simple and efficient messy system using a difference in the output sequence. To meet the requirements of image encryption, we create a new coding system for linear and nonlinear structures based on the generation of a new key based on chaotic maps.The design uses a kind of chaotic maps including the Chebyshev 1D map, depending on the parameters, for a good random appearance. The output is a test in several measurements, including the complexity of the standard balance and time execution.The results show that any change in input will change the output and the time required for the application requires only parts of the minute.The output is passed through the exponential function [exp (X))] to obtain a wide range of input. The result is then set to machine words to fit the desired range of multicast used.The next step is the output of machine words that will be used as input to the array that we have structured to generate the key. The key is converted to a sequential element into an element with an ordinary image to produce the encrypted image. Furthermore, keystream succeeded by passing tests (NIST statistical package tests for random). Finally, the real-time image encoding of the corresponding algorithm was applied; preliminary results show that the proposed algorithm has good coding strength with added benefit that resists security analysis.